(3GdeSGgeGJ GdYjfjI aj GdTQcGJ GdJLGQjI (B:s (3OQGSI ebGQfI (B/s - (3hdO Gejf, eMeO aGd GdMSfs ((3HjQhJ(B: s (3eLO GdeDSSI GdLGeYjI(B, s, 2009)
(3MeGjI Mbhb GdZjQ ef NdGd ENVGY GdeSGgeI HGdYjf ddJbhje HGdJWQb Edi Jbhje GdeSGgeGJ GdYjfjI h bUhQGdfXGe GdbGfhfj ddJbhje h GdMeGjI ef NdGd EbQGQ eHOCGdJSOjO GdahQj ddeSGgeIGdYjfjI HGdJWQb Edi eOi bGHdjI GdeSGgeI GdYjfjI ddJSOjO GdahQj h JMbjb GdahQjI dMeGjI Mbhb GdZjQ , GdJhSY aj GdJRGeGJ GdeSGge HGdYjf HGdJWQb Edi JTHjg GdeSGge Ydi hLg GdJedjc HGdHGFY h JTHjg GdeSGge HGdYjf Ydi hLg GdGfJaGY HGdecQj , GdJVjjb aj GdMbhb GdeJQJHI Ydi GdeSGgeI HGdYjf HGdJWQb Edi GdbjhO GdhGQOI Ydi GdMbhb ZjQ GdeGdjI h GdbjhO GdhGQOI Ydi GdMbhb GdeGdjI dddeSGge HGdYjf (B.s
Keywords: (3GdCYeGd GdJLGQjIs; (3GdTQcGJs; (3GdeSGgehfs